Stem/Progenitor Cells and Their Therapeutic Application in Cardiovascular Disease - Hou, Yuning; Li, Chunying (Frontiers in Cell and Developmental Biology, 2018)
Cardiovascular disease is the leading cause of death in the world. The stem/progenitor cell-based therapy has emerged as a promising approach for the treatment of a variety of cardiovascular diseases including myocardial infarction, stroke, peripheral arterial disease, and diabetes. An increasing number of evidence has shown that stem/progenitor cell transplantation could replenish damaged cells, improve cardiac and vascular functions, and repair injured tissues in many pre-clinical studies and clinical trials. In this review, we have outlined the major types of stem/progenitor cells, and summarized the studies in applying these cells, especially endothelial stem/progenitor cells and their derivatives, in the treatment of cardiovascular disease. Here the strategies used to improve the stem/progenitor cell-based therapies in cardiovascular disease and the challenges with these therapies in clinical applications are also reviewed.